THE HISTOLOGICAL STRUCTURE OF LONG BONES - Mirtalipova Mokhizoda; Abdujabborova Adashoy (Modern American Journals, 2025)
This study provides a detailed examination of the histological (tissue-level) structure of long bones. It analyzes, at the microscopic level, the main structural components of bone tissue — osteons, Haversian canals, lamellar layers, osteocytes, lacunae, and canaliculi. The differences between compact (dense) and spongy (cancellous) bone tissue, their functional significance, and their role in the bone regeneration process are also highlighted. The study includes information on the vascularization of bone tissue, the intercellular matrix, and mineral components, as well as their impact on bone strength. This topic holds significant scientific and practical value for students studying anatomy, histology, and medicine.
Keywords: Bone tissue, osteon, Haversian canals, osteocyte, compact bone, spongy bone, lamellar layer, lacuna, canaliculus, blood vessels (in bone), bone regeneration, physiological role of bone.